The Mediating Effect of Well-Being, Happiness, and Trust in the Relationship Between Work-Life Balance and Work Effectiveness in Seafarers - Nihan Senbursa PhD; Emre Dunder PhD (SAGE Publishing, 2024)
In the contemporary global context, seafarers persist as the uncelebrated heroes of international trade, despite their substantial contributions. The current estimate places the number of STCW- certified officers at 857 540, reflecting a notable increase of 10.8% since 2015. Nevertheless, there is a growing recognition of the imperative to accord specific attention to seafarers' mental and physical well-being. During their tenures aboard ships, seafarers confront various challenges, including psychological well-being, work-life imbalance, dissatisfaction, diminished performance, and a sense of mistrust toward the organizational framework. The primary objective of this research is to scrutinize the nexus between work-life balance and work effectiveness, exploring the mediating roles of psychological well-being, organizational happiness, and organizational trust. A questionnaire-based survey is meticulously crafted to achieve this, employing a dataset comprising 420 seafarers engaged in diverse vessel types in Turkey, operating under both Turkish and international flags. Methodologically, structural equation modeling and correlation analyses are executed to assess the formulated research hypotheses rigorously. The empirical findings of this research reveal noteworthy mediating roles: psychological well-being exhibits a complete mediation effect, organizational happiness demonstrates a full mediation effect, and organizational trust manifests a partial mediation effect. These outcomes underscore the nuanced interplay between work-life balance and work effectiveness in the seafaring context. The implications of these findings extend significantly to the maritime sector and industry, accentuating the imperative for targeted interventions to enhance the well-being and performance of seafaring professionals.